Metodología para recuperar puentes y pilares mediante muros de concreto en el tajo 9910-4, nivel 2995, contrata Divino Jesús, Pataz - Rodriguez Baca, Miguel Aníbal (2023)
The main objective of the research was to apply the methodology of concrete walls to recover bridges and pillars in TJ 9910-4, Nv.2995 of Contrata Divino Jesus, Pataz 2022. The methodology used was of descriptive design, of the applicative type. The population consisted of all the contracts of the U.P. Santa María de la C.M. Poderosa, and the sample consisted of the TJ 9910-4 of Nv.2995 of the Divino Jesús contract. The results obtained were that the operation of the recovery stage of bridges and pillars with concrete walls was evaluated, where initially there were a total of 12 natural pillars, also, there were 9 openings, where the total area was 1042.99 m2, the average height was 5.52 m, and the total volume was 3760.08 m3. Likewise, the recovery of pillars was carried out through 7 accesses, being access 7 the one that allowed the recovery of 11 pillars. Also, the mechanical properties of the concrete were determined, which was necessary to have a resistance of 175 kg/cm3 for a Wood pack of 1x1m with a height of 1.5m to withstand a pressure of 180 ton/m2. Likewise, the geomechanical and stability conditions of the rock mass were verified, which at the beginning had a safety factor of 0.95 with a maximum plastic radius of 4.12 meters, which later, when recovering the pillars, the safety factor varied between 0.95 and 1.26 but the plastic radius increased by 10 meters, which later had to distribute the efforts in natural and artificial pillars. Finally, it is concluded that, with the evaluation of the operation in the stage of pillar recovery, mechanical properties of concrete, geomechanical conditions and rock mass stability, it was possible to apply the methodology of concrete walls to recover bridges and pillars in TJ 9910-4, Nv. 2995 of Contrata Divino Jesus, Pataz 2022.